Role of Pradhamana Nasya in Tridoshaja Pratishyaya w.s.r to Chronic Sinusitis (AYUSHDHARA, 2022)
Sinusitis is considered as one of the most common clinical conditions among chronic diseases. Modification in lifestyle, rise in the cases of antibiotic resistance, deviated nasal septum, nasal polyps, tumors etc. are responsible for increased prevalence of sinusitis. Sinusitis affects 10-30% population whereas Chronic Sinusitis affects approximately 12.5% population each year. Women are more affected in comparison with men. Feature of Sinusitis can be co-related with Tridoshaja Pratishyaya. Acharya Sushruta has mentioned Pratishyaya under 31 Nasagata rogas. In modern science, sinusitis is managed with antibiotics, nasal decongestants sprays, corticosteroids, analgesics etc. Excessive use of decongestant sprays can cause rebound congestion. Person may become resistant to antibiotics. Repeated attacks of sinusitis and fear of surgery may cause depression to the patient. Permanent cure of sinusitis can be achieved through Ayurvedic management. In Brihat Samhita, Nasya has been considered as effective treatment modality for all kinds of Urdhava Jatrugata rogas (diseases of supra clavicular region). Acharya Charaka in Chikitsa Sthana has mentioned Pradhamana Nasya for the management of Kapha Pradhan Pratishyaya.  In the present case study, a patient with the symptoms of Kapha Pradhan Tridoshaja Pratishyaya was treated with Manashiladi churna Pradhamana Nasya. Patient got complete relief in sign and symptoms.